ORIENTAREA DE MARKETING CA STRATEGIE DE DEZVOLTARE A BIBLIOTECILOR UNIVERSITARE DIN REPUBLICA MOLDOVA - CHERADI, Natalia (BIBLIOPOLIS, 2020)
The goal of research is to analyze the peculiarities of marketing orientation of the library in order to establish some methodological criteria for inserting the marketing tools in university libraries in the Republic of Moldova, to determine the factors that contribute to the estimation of the documentary heritage and the development of competitive information services. Research objectives: examining the theoretical and methodological framework on marketing extension in information research services; elucidating the impact of marketing environment on university libraries operations; identifying the factors of impact on the behavior of the user of information research services; identifying the marketing mix and integrating its components into the university library system in Moldova. Practical utility of research lies in the fact that the author has come up with the measures that would ensure the implementation of marketing technologies in the library sphere: developing the nomenclature of the library services; developing the methodology for calculating the tariffs of the library services; identifying the most efficient methods of distribution and promotion of information resources and services; formulating the regulatory framework of marketing within academic libraries; developing some suggestions on improving the image and information services in academic libraries in Moldova.